ANALISIS PERBANDINGAN CUSTOMER EXPERIENCE DAN CUSTOMERS PERCEIVED QUALITY PADA KEPUASAN KONSUMEN SOLO STEAK DAN STEAK MOEN MOEN MOJOSONGO - Arneta Alfiana Kusumaningtyas; Tiara Rusida Rahmawati; Dian Oktaviyani; Devina Safa Felisya; Marjam Desma Rahadhini (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study underscores the importance of customer experience and perceived quality in determining the level of customer satisfaction in the highly competitive restaurant sector. The purpose of this study is to explore the significant differences and relationships between customer experience and perceived quality at Solo Steak and Steak Moen Moen Mojosongo. The methodology used in this study is a quantitative approach, where data were collected through questionnaires. The information collected was then analyzed using validity, reliability, and independent sample t-tests. The results of this study indicate significant differences in customer experience and perceived quality between the two restaurants, while also indicating a positive relationship between the two variables. These findings can be a guideline for restaurant management in improving service strategies and customer experience and can also be a reference for future research in the field of restaurant marketing